2004
DOI: 10.1097/01.alc.0000107199.26934.46
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Negativity: No Difference Between Controls and Abstinent Alcoholics

Abstract: Background-A number of studies have examined the amplitude of the mismatch negativity (MMN) evoked potential as a measure of a brain inhibitory deficit in alcoholics or those at risk for alcoholism. The current study examined MMN in alcoholics abstinent an average of 6.7 years (with a minimum of six months abstinence) compared to controls. This study examined the association of MMN with alcoholism family history density, with indices of the presence and severity of externalizing disorders (a risk-factor for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
1
12
2
1
Order By: Relevance
“…The TxNA sample came from a population with a history of early abusive drinking (in the first 5 years immediately after meeting criteria for heavy alcohol consumption) that was 30 -40% less in average and peak dose than treated samples (Fein and Landman, 2005). They had an increased rate of externalizing symptoms and psychological evidence of deviance proneness compared with controls, although these rates were markedly less than those of treated samples (Fein et al, 2004). Our hypothesis is that the population studied is composed of individuals with less severe manifestations of the nexus described above who have later developed alcohol dependence but no other diagnosable psychiatric or substance abuse disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The TxNA sample came from a population with a history of early abusive drinking (in the first 5 years immediately after meeting criteria for heavy alcohol consumption) that was 30 -40% less in average and peak dose than treated samples (Fein and Landman, 2005). They had an increased rate of externalizing symptoms and psychological evidence of deviance proneness compared with controls, although these rates were markedly less than those of treated samples (Fein et al, 2004). Our hypothesis is that the population studied is composed of individuals with less severe manifestations of the nexus described above who have later developed alcohol dependence but no other diagnosable psychiatric or substance abuse disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The automatic stimulus change detector mechanism associated with MMN generation is impaired in chronic alcoholics over the age of 40, suggesting that the neurotoxic effects of chronic consumption of alcohol are more prone to appear after a critical age (Polo et al, 1999). One study showed no MMN differences between controls and alcoholics who were abstinent for an average of 6 years (Fein et al, 2004), while another (Pekkonen et al, 1998) observed that increasing durations of abstinence reduced the MMN amplitude, perhaps indicating improved efficiency of covert processes upon abstinence. Ahveninen et al (2000) found significantly enhanced MMN amplitudes to deviant sounds that correlated with reaction time lag caused by deviants, indicating pronounced distractibility and impaired reorienting to the relevant task in alcoholics.…”
Section: Chronic Alcoholism and Neuroelectrophysiologymentioning
confidence: 99%
“…Also, it should be noted that MMN data suggest some recovery for chronic alcoholism, as no difference in amplitude and latency between a control group and a group of alcoholics displaying a minimum of 6 months of abstinence has been evidenced. [56][57][58] The P300…”
Section: Mismatch Negativitymentioning
confidence: 99%